Applied multimodal for emotion recognition - Nguyen , Thi Khanh Hong; Vo , Thi Huong; Le , Huu Duy (Journal of Technical Education Science, 2020)
Detecting and classifying emotions has currently become an important item of research and life. The more detailed and accurate emotion recognition system is due to the development of various fields such as electronics, sensors or computer engineering. Emotion recognition methods are studied using different data collection methods and one of the most popular and effective methods is physical – bio sensors. Physical – bio sensor based approaches can provide more accurate, sustainable biological information with external influences and interferences, especially when we compared with other approaches such as image processing, video processing. In this paper, a method of classifying and assessing emotions based on a combination of signals collected from physical – bio sensors, video collection and machine learning are supposed. Specifically, we will describe the platform of a physical – bio signal collection system, the process of collecting information and the information processing system used to identify how emotional behavior is characterized. We have also shown that a combination modals of physical – bio sensor acquisition systems, video processing based on machine learning methods can provide identification performance with an accuracy of 83.2%